The Effect of Game-Based Learning Through the Snake and Ladder Game on Students’ Speaking Skills - M. Labib Al Halim; Muhammad Ainul Yaqin (Reforma : Jurnal Pendidikan dan Pembelajaran, 2022)
Speaking was crucial skill to be learnt by student in order to talk with others from around the world. Students would need to rehearse to be able to express their ideas in English. The students’ Speaking skill was developed in the classroom when they have English class though in daily activities, they did not speak English. It made speaking as one of the most challenging things for students to grasp. The use of a good teaching method or media was really important in the teaching speaking process. The snake and ladder game was used as a medium by the researcher. This research was using experimental research with pre-experimental design (one group pretest-posttest). The data itself was analysed by using statistical through SPSS program. The participants of the research were the eleventh grades students of MA Falahiyah Lamongan. The data showed the students’ basic speaking skill of eleventh grades students in MA Falahiyah Lamongan were poor, because most of the students score were under the minimum score criteria. There were only 13% students passed the test. After getting the treatment,  the result of the finding of post-test, the data showed the students’ speaking skill were improved because most of the students got enough score to complete the test. The result of the calcutaion of paired sample t-test with the sign (2 tailed) the result was .000, it was lower than 0.05 as level of significant. It means that the use of game-based learning through the snake and ladder game to teach speaking gave significant effect on students’ speaking skills.